2008
DOI: 10.1021/nl802269a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Size Control and Polymorphism in Viral Capsid Assembly

Abstract: We simulate the assembly dynamics of icosahedral capsids from subunits that interconvert between different conformations (or quasi-equivalent states). The simulations identify mechanisms by which subunits form empty capsids with only one morphology, but adaptively assemble into different icosahedral morphologies around nanoparticle cargoes with varying sizes, as seen in recent experiments with brome mosaic virus (BMV) capsid proteins. Adaptive cargo encapsidation requires moderate cargo-subunit interaction str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
124
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(137 citation statements)
references
References 50 publications
13
124
0
Order By: Relevance
“…403 Intrinsic curvature of capsomer-capsomer junctions predisposes the final size of capsids to be formed, while a flexibility of these connections permits the formation of shells of different sizes, e.g. for in vitro capsid assembly around artificial cores 428,429 and polymers. 398 Capsomers of many viruses bear rather high electric charges on their surfaces and contain ionizable groups, 430 that are often distributed quite non-uniformly, see Fig.…”
Section: B Capsid Self-assembly and Shell Elasticitymentioning
confidence: 99%
“…403 Intrinsic curvature of capsomer-capsomer junctions predisposes the final size of capsids to be formed, while a flexibility of these connections permits the formation of shells of different sizes, e.g. for in vitro capsid assembly around artificial cores 428,429 and polymers. 398 Capsomers of many viruses bear rather high electric charges on their surfaces and contain ionizable groups, 430 that are often distributed quite non-uniformly, see Fig.…”
Section: B Capsid Self-assembly and Shell Elasticitymentioning
confidence: 99%
“…In self-assembly, this is known as "kinetic trapping." In recent years, several studies 4,5,[10][11][12][13][14][15][16][17][18] have observed that self-assembly is most efficient when structures are stabilised by large numbers of relatively weak interactions. In particular, while strong interparticle bonds stabilise the ordered equilibrium state, they are also associated with kinetic trapping effects that frustrate the assembly process.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest models represent the capsomers as isotropic bodies, but they require additional geometrical constraints such as a template of the virus capsid [14][15][16][17][18][19] . In other more complex models each capsomer is represented as a discrete set of either isotropic 17,[20][21][22][23][24] or anisotropic interaction centres [25][26][27] , or as a continuous body of interaction points plus some extra discrete centres 28 .…”
Section: Introductionmentioning
confidence: 99%